THE ROLE OF NURSING IN THE EARLY DETECTION AND PREVENTION OF PREGNANCY-INDUCED HYPERTENSION AMONG PREGNANT MOTHER - V. Manjula; Dr. Sathiyalatha Sarathi; Dr. V. Hemavathy (The Bioscan, 2025)
Introduction: Pregnancy-induced hypertension (PIH) is a maternal hypertension syndrome diagnosed during the later part of pregnancy, usually after the 20th week of gestation. PIH can lead to severe complications for both the mother and the fetus. Early identification and management of PIH is crucial to prevent adverse maternal and fetal outcomes Aim: To assess awareness and risk Indicators for Early Detection of Pregnancy-Induced Hypertension Methods: This research employed a cross-sectional descriptive design, and the study was carried out at some selected Primary Health Centers (PHCs). The eligible participants for the study were pregnant women, with those who had other complications or those who did not give their consent being ineligible. The sample size was determined using the power analysis to be 60. The method used for selecting participants was based on convenient sampling method. This study received Ethical approval from the Institutional Ethical Committee of Sree Balaji Medical College & Hospital (ECR/719/Inst/TN/2015/RR-21) and an informed written consent was also taken from all participants. Results: In terms of PIH risk indicators, 33.3% had raised systolic blood pressure (≥130 mmHg), 25% had raised diastolic blood pressure (≥90 mmHg), and 16.7% exhibited proteinuria. Common symptoms included rapid weight gain, swelling of hands/feet, and obesity (16.7%). A history of PIH or family hypertension was reported by 20%, while 13.3% had elevated fasting glucose levels (>92 mg/dL). Regarding awareness, 58.3% had heard of PIH, but only 50% knew its symptoms. While 66.7% understood the risks of high blood pressure and 75% monitored their blood pressure, fewer were aware of PIH risks (46.7%) or preventive lifestyle changes (43.3%). Most women recognized the importance of prenatal checkups (83.3%), but 40% were unaware that PIH could occur without prior hypertension. Additionally, 73.3% knew where to seek help for PIH symptoms. Conclusion: The study concluded that through regular antenatal care, risk factor assessment, patient education, and interdisciplinary collaboration, nurses can contribute to the reduction of maternal and fetal morbidity and mortality associated with this condition.